1989
DOI: 10.1007/bf03005435
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of syringes

Abstract: Contamination of syringesTo the Editor:The recent article by Lessard etal. showed the risk to the patient of bacterial contamination with multiple use of syringes to be negligible but emphasized the risks from viral contamination.l A questionnaire was distributed to all members of anaesthesia departments of the Universities of Pittsburgh and Michigan in the general adult, paediatric and obstetric divisions (five hospitals total) to quantitate the frequency of common syringe techniques. Anonymous responses were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…However, other studies have shown that the rate at which blood contaminates the intravenous tubing used for anesthesia is substantial (0.3 to 3.3 percent of cases). [21][22][23] The presence of a check valve and the changing of the needle do not affect the rate at which intravenous lines and syringes become contaminated -a point that should be emphasized, because multidose vials are very commonly used in anesthesia. [21][22][23] Moreover, because the assessment of risk factors is not a reliable predictor of which patients have chronic viral infection, the prac-tice of following strict procedures for anesthesia only in patients with known infections has little rationale and should be abandoned.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have shown that the rate at which blood contaminates the intravenous tubing used for anesthesia is substantial (0.3 to 3.3 percent of cases). [21][22][23] The presence of a check valve and the changing of the needle do not affect the rate at which intravenous lines and syringes become contaminated -a point that should be emphasized, because multidose vials are very commonly used in anesthesia. [21][22][23] Moreover, because the assessment of risk factors is not a reliable predictor of which patients have chronic viral infection, the prac-tice of following strict procedures for anesthesia only in patients with known infections has little rationale and should be abandoned.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the written recommendations of professional associations, such as the American Society of Anesthesiologists 28 and the American Association of Nurse Anesthetists, 29 which specifically advocate the use of aseptic techniques during the handling of medications, several authors have reported poor compliance with aseptic techniques and infection-control practices by anesthesia personnel. [30][31][32][33][34][35][36] Contamination of multidose vials, 15,37,38 use of a single syringe to administer medication to different patients, 39 assembling infusion equipment far in advance of use, 40 and contamination of syringes and catheters 38 have all been implicated in other outbreaks. Studies show that reuse of multidose vials can cause contamination of the medication in the vial 15 and that contamination can occur during the opening of a glass vial whose surface has not been disinfected.…”
Section: Discussionmentioning
confidence: 99%